VD_FINDINFO Arrêt / 2018 / 603 vom 2. Juli 2018 - VD Tribunal cantonal (2018)
AIASSURANCE, RENTE D'INVALIDITÉ, ÉVALUATION DE L'INVALIDITÉ, FORCE PROBANTE, DROIT D'ÊTRE ENTENDU | 29 Cst., 17 al. 1 LAI, 28 LAI, 17 LPGA, 6 LPGA, 8 al. 1 LPGA